Pengaruh Literasi Keuangan, Teman Sebaya, Sosialisasi Orang Tua dan Self Control Terhadap Saving Behavior Siswa SMK Jurusan Akuntansi di Kabupaten Sukoharjo - Hendratmoko, Christiawan; Wardana, Eko Kusuma (Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital, Ekonomi Kreatif, Entrepreneur (JEBDEKER), 2022)
This research aims to determine the influence of financial literacy, peer-to-peer socialization and self control of the saving behavior of SMK Accounting department in Sukoharjo district. The population in this study was a SMK accounting department student in Sukoharjo regency with many samples taken as many as 94 respondents, which were determined using stratified proportional random sampling technique. The variables used in this study are financial literacy, peer, parental socialization, self control, and saving behavior. The primary data collection method is performed using the questionnaire method with the Likert scale. Analysis of data conducted by test methods of data instruments, classical assumption tests and multiple regression analysis. The results showed that financial literacy has no significant positive effect on saving behavior, peers significantly positively influence the saving behavior, the socialization of positive influence is not significant to Saving behavior, self control has significant positive effect on saving behavior, with coefficient of determination (R2) of 63.0%. The advice in this study is that students in the accounting department at Sukoharjo district need to maintain self control of the saving behaviour and maintain a positive relationship that has been positively impact, as well as for research should further add to the variables and broaden the coverage area for improvement in similar study.